Identifying Risk-Taking Behavior and Prudent Asset Allocation in Pension Funds in Indonesia - Prabowosunu, Mohammad Alvin; Siregar, Reza Yamora; Melati, Rosi; Hadrian, Devan; Ronaldo, Rizky Rizaldi (UI Scholars Hub, 2024)
This research aims to investigate asset allocation strategies in the pension fund industry in Indonesia in relation to liability profiles and risk-taking behavior. Utilizing data on market returns for each asset class and several financial indicators of pension funds, we applied the risk-taking behavior model proposed by Andonov & Rauh (2022) and a modified model to observe the Liability-Driven Investment (LDI) strategies of pension funds in Indonesia. We discovered that private defined contribution pension fund schemes (PPIP) tend to exhibit higher risk-taking behavior, primarily through investment allocation in equities. On the other hand, private defined benefit pension funds (PPMP) demonstrate a less aggressive risk-taking approach, allocating investments in bonds and cap/blue-chip stocks. PPMP also indicates relatively better implementation of the LDI strategies by considering the sensitivity of long-term bonds concerning return on investment (ROI).